2011
DOI: 10.1002/jcu.20809
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic appearance of a giant appendicular mucocele

Abstract: Mucocele of the appendix is a rare but well-known entity. Accurate preoperative diagnosis of this surgically curable entity is very important to prevent intraoperative rupture. With multimodality approach using ultrasound and CT, it has been possible to preoperatively diagnose mucocele of the appendix. We describe the ultrasound and CT findings of a giant appendicular mucocele that led us to the correct preoperative diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The typical CT appearance of an appendiceal mucocele is a large and well-encapsulated cystic mass in the expected region of the appendix; calcifications of the cyst wall are highly specific to this lesion and a useful feature for differentiating the cyst from an abscess [1, 17, 18]. Usually, CT is considered the most informative imaging technique although the diagnosis is more difficult when calcifications are absent and it can fail to identify the organ of origin, as demonstrated in the literature [3, 19, 20]. In the case of giant mucoceles, the diagnostic problem may be even more challenging because of the difficulties in defining the precise anatomic relationship with the cecal region and also for the fact that most CT findings are insensitive [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical CT appearance of an appendiceal mucocele is a large and well-encapsulated cystic mass in the expected region of the appendix; calcifications of the cyst wall are highly specific to this lesion and a useful feature for differentiating the cyst from an abscess [1, 17, 18]. Usually, CT is considered the most informative imaging technique although the diagnosis is more difficult when calcifications are absent and it can fail to identify the organ of origin, as demonstrated in the literature [3, 19, 20]. In the case of giant mucoceles, the diagnostic problem may be even more challenging because of the difficulties in defining the precise anatomic relationship with the cecal region and also for the fact that most CT findings are insensitive [21].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, during ovarian cancer surgery, appendicectomy is frequently required to rule out the presence of microscopic metastasis or of a primary appendiceal cancer and to achieve optimal cytoreduction. Coexistence with colon adenocarcinoma and endometrial adenocarcinoma has also been reported in the literature, although rarely [20, 22, 23]. A careful preoperative and intraoperative evaluation are required considering the mucocele's potential to develop cancer, the risk of rupture that may lead to the catastrophic complication of pseudomyxoma peritonei, and the documented association with coexistent pathology [10, 15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…This, content may be layered, causing the 'onion skin' sign that represents the concentric pattern of mucoid material in the lesion (11,12,13). Similar to CT, an important feature is the lack of inflammation, with no wall thickening (> 6 mm) as seen in acute appendicitis.…”
Section: Clinical Presentation and Treatment Optionsmentioning
confidence: 99%
“…It is found in less than 2% of appendicectomy specimens [2] and accounts for 0.5−1% of all gastrointestinal (GI) malignancies [35]. Malignancy within a mucocele has an excellent prognosis with over 90% survival [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…If a mucocele is suspected, a more extensive surgical approach may be required to reduce the risk of complications and achieve better oncological outcome [4, 5]. Pseudomyxoma peritonei can occur due to rupture or invasion of the mucocele when there is a delay in intervention.…”
Section: Introductionmentioning
confidence: 99%